(untitled) (Medical Forum Monthly, 2024)
ABSTRACT Objective: Specific objective of this study was to determine the oxidative stress and anti-oxidant level in aging among 30 to 62 years of healthy male and female of Peshawar City. Study Design:-Descriptive Study. Place and Duration of Study: This study was conducted in Jinnah Medical College, Peshawar with collaboration of Faculty of Pharmacy. Gomal University D.I. Khan from January 2013 to May 2014. Materials and Methods:-Total 180 study. Subjects were examined and standardized according to essential parameter of age and sex with no history of any disease and were not talking any medicine with same Scio-economic factor used for analysis. 90 male divide into three (03) Groups A,B,C and 90 female Subjects was also divide in 3 Groups A,B,C. Serum Ferric Reducing Antioxidant Power (FRAP) assay of Vitamin C, Vitamin E and Glutathione was determined and analyzed. Results:-Results were observed with the FRAP values of Vitamin C, E and Glutathione values which are summarized in the table in Show in Figure. Vitamin E, a Secondary antioxidant is very important for generation of other antioxidants. Conclusion: The decrease of value also indicate that define system is deceased during aging the GSH is an important for defense system of the body. Also decreased during aging, specially in old age after 40 years. It is important to use the supplement with diet to fulfill deficiency of their secondary antioxidant.